MOLECULAR MARKER ANALYSIS OF A QTL REGION FOR GRAIN SIZE IN BASMATI RICE - V. L. N. REDDY, D. A. K. DEBORAH, G. ANURADHA, K. RADHIKA and (The Journal of Research, PJTSAU, 2019)
Basmati rice is a unique varietal group possessing unique grain quality traits. Breeding of new varieties having Basmati grain quality characters can be greatly facilitated by the use of molecular markers tightly linked to these traits. Hence, in the present investigation 155 recombinant inbred lines (RILs) developed from a cross between Basmati 370 and Jaya were used for molecular analysis of a major QTL for grain size in Basmati rice identified in F2 population. For this study, SSR and InDel markers present in and around the QTL region were used. Transgressive segregants of 45.8% for grain length, 21.93% for grain breadth and 12.25% for LB ratio were observed. All the three traits exhibited normal distribution indicating quantitative inheritance of these traits. Correlation analysis revealed a high significant negative association of grain length-breadth ratio with grain breadth and significant positive correlation with grain length. Out of 53 markers used, 23 (43.40%) markers were polymorphic among the parents. QTL mapping study revealed a minor QTL, qGL5.1 in the marker interval of RM6024 and RM1237 for grain length with Phenotypic Variance (PVE) of 3.7% by IM and a QTL, qGB5.1 for grain breadth with PVE of 3.58% by CIM and 4.51 % by IM and a QTL qGLB5.1 for grain lengthbreadth ratio with PVE of 11.8 % by IM in the marker interval of RM1237 and RM18582. In the present study, the QTL cluster region was narrowed down from 26.5cM to 15.6cM. These stable QTLs also facilitate development of Near-isogenic lines and advanced breeding lines.